Investigation of posibility of energy transfer to plasma ions by oscillations with large amplitude on frequency of electron cyclotron resonance in magnetic trap - Antipov, V.S.; Antonov, A.N.; Buts, V.A.; Kovalchuk, I.K.; Kornilov, E.A.; Vinokurov, V.A. (Вопросы атомной науки и техники, 2018)
Process of action of powerful transverse electromagnetic wave on plasma in the magnetic trap is studied theoretically and experimentally. Interaction of wave-wave type is taken into account in the theoretical model. Investigation is based on three wave interaction. The cascades of three wave interaction described too. In the experiment the
wave spectrums exciting in plasma were studied and it was shown enough fast appearance of energetic ions flows.
There is a enough good agreement theoretical and experimental results. Теоретично та експериментально вивчається процес впливу потужної поперечної електромагнітної хвилі
на плазму в магнітній пастці. У теоретичній моделі враховується взаємодія типу хвиля-хвиля. Дослідження
ґрунтується на трьоххвильовій взаємодії. Розглянуто також каскади трьоххвильової взаємодії. В експерименті вивчено спектри хвиль, що збуджуються в плазмі, і показано досить швидку появу потоків високоенергетичних іонів. Є гарне якісне узгодження теоретичних та експериментальних результатів. Теоретически и экспериментально изучается процесс воздействия мощной поперечной электромагнитной волны на плазму в магнитной ловушке. В теоретической модели учитывается взаимодействие типа волна-волна. Исследование основано на трехволновом взаимодействии. Рассмотрены также каскады трехволнового взаимодействия. В эксперименте изучены спектры волн, возбуждаемых в плазме, и показано достаточно быстрое появление потоков высокоэнергетических ионов. Имеется хорошее качественное согласие теоретических и экспериментальных результатов.